2021
DOI: 10.1002/wer.1599
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic understanding of the pollutant removal and transformation processes in the constructed wetland system

Abstract: Constructed wetland systems (CWs) are biologically and physically engineered systems to mimic the natural wetlands which can potentially treat the wastewater from the various point and nonpoint sources of pollution. The present study aims to review the various mechanisms involved in the different types of CWs for wastewater treatment and to elucidate their role in the effective functioning of the CWs. Several physical, chemical, and biological processes substantially influence the pollutant removal efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 224 publications
0
10
0
Order By: Relevance
“…According to the United Nations, an estimated 80% of all industrial and municipal wastewater in the developing world is released into freshwater bodies without any prior treatment [18]. Heavy metal removal can be achieved through different physical, chemical and biological methods such as fungal remediation [19], microbial remediation [12,20], phytoremediation [21,22], adsorption [23,24], flotation, coagulationflocculation [25], chemical precipitation or ion exchange [26]; selection between these may be based on the nature and quantum of the pollution load and merits/demerits of decontamination processes along with other factors. It is noted that removal of heavy metals from water/wastewater is still an evolving research area, and there is wide scope for case-specific evaluation, optimization and integration of new and/or available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…According to the United Nations, an estimated 80% of all industrial and municipal wastewater in the developing world is released into freshwater bodies without any prior treatment [18]. Heavy metal removal can be achieved through different physical, chemical and biological methods such as fungal remediation [19], microbial remediation [12,20], phytoremediation [21,22], adsorption [23,24], flotation, coagulationflocculation [25], chemical precipitation or ion exchange [26]; selection between these may be based on the nature and quantum of the pollution load and merits/demerits of decontamination processes along with other factors. It is noted that removal of heavy metals from water/wastewater is still an evolving research area, and there is wide scope for case-specific evaluation, optimization and integration of new and/or available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the water concentrations of Al, and the rest of the elements, are efficiently reduced as water flows through the different sectors of the CW. Several studies have reported the reduction of heavy metals through microbial and plant biomass in CWs, by means of two main mechanisms: the active one being energy-dependent bioaccumulation, and the passive one energy-independent biosorption (by the adsorption mechanism) (Malyan et al 2021 ; Yu et al 2021 ). For example, Bianchi et al ( 2021 ) reported biosorption through macrophyte species, such as Phragmites australis (the role of reed biomass as a biosorbent material yields the removal of Zn by 73%, under optimum dose and experimental conditions).…”
Section: Discussionmentioning
confidence: 99%
“…But the water course throughout the different sectors of the CWs causes the decrease in the prevalence of most pesticides. Several processes occurring within the CWs, such as adsorption, hydrolysis, microbial degradation, sedimentation, photolysis, and plant uptake play an important role in said removal of pesticides in CWs (Vymazal and Březinová 2015 ; Malyan et al 2021 ). Moreover, the concentrations of pesticides that have been quantitatively analyzed (Table 2 ) are far below the toxic concentrations for aquatic organisms that have been reported in several studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution to mitigate pesticide pollution from vineyard runoff water is detention ponds (DPs) (e.g., Maillard et al., 2011 ; Maillard and Imfeld 2014 ; Liu et al., 2019 ; Malyan et al., 2021 ). DPs are engineered systems designed to use nature-based solutions such as adsorption followed by sedimentation, physicochemical and microbial degradation and plant uptake ( Vymazal 2005 ), depending on the hydraulic residence time (HRT) and thus water inputs.…”
Section: Introductionmentioning
confidence: 99%